Analysis of the Role of Social Media in Increasing Sales Outcomes among MSMEs in Baubau City - Ahmad Saiful (Institute Journal and Publication Muhammadiyah University of Buton, 2025)
This study examines the role of social media in increasing sales outcomes among Micro, Small, and Medium Enterprises (MSMEs) in Baubau City. In the context of digital transformation, social media has become an important marketing tool that enables MSMEs to promote products, interact with customers, and expand market reach more efficiently. However, the effectiveness of social media in supporting sales performance at the local MSME level remains an important issue to investigate. This study employed a quantitative approach with a survey design. The population consisted of MSME owners in Baubau City who actively used social media for business purposes, while the sample was selected through purposive sampling. Data were collected using a structured questionnaire and analyzed through descriptive and inferential statistical techniques. The findings reveal that social media plays a significant role in improving sales outcomes among MSMEs in Baubau City. Platforms such as WhatsApp, Facebook, Instagram, and TikTok were widely used for promotional activities, customer communication, and product visibility. The study found that consistent posting, attractive content, and active customer interaction contributed positively to increasing customer inquiries, purchase transactions, and repeat orders. Social media also helped MSMEs broaden their market reach beyond their immediate business environment. Nevertheless, the effectiveness of social media was influenced by several supporting and inhibiting factors, including digital literacy, content creativity, product quality, time constraints, and limited digital skills. In conclusion, social media is a strategic instrument for strengthening MSME sales performance and competitiveness in Baubau City. Therefore, efforts to improve the digital capacity of MSME actors are essential to ensure the optimal and sustainable use of social media in business development.